2017
DOI: 10.1177/0003319717732237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicorandil Administration on Preventing Contrast-Induced Nephropathy: A Meta-Analysis

Abstract: Several studies have investigated the effect of nicorandil on contrast-induced nephropathy (CIN) in patients undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI). However, the final results of these trials are not identical. This meta-analysis evaluated the role of nicorandil administration on CIN prevention. We searched databases to find randomized controlled trial (RCT) comparing nicorandil with hydration versus conventional hydration therapy on preventing CIN. Finally, 5 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…25 A meta-analysis found that, compared to conventional hydration, nicorandil therapy could significantly reduce CIN risk in patients undergoing coronary intervention. 26 A recent study demonstrated the preventive effects of alprostadil on the development of CIN in patients with renal insufficiency undergoing percutaneous coronary intervention (PCI). 27…”
Section: Discussionmentioning
confidence: 99%
“…25 A meta-analysis found that, compared to conventional hydration, nicorandil therapy could significantly reduce CIN risk in patients undergoing coronary intervention. 26 A recent study demonstrated the preventive effects of alprostadil on the development of CIN in patients with renal insufficiency undergoing percutaneous coronary intervention (PCI). 27…”
Section: Discussionmentioning
confidence: 99%
“…The present meta-analysis has some limitations. First, we lacked relevant information to clarify whether cardiovascular comorbidities (age and diabetes), 12,36 the dose and frequency of nicorandil administration, 11 and contrast volume 37 have an impact on the efficacy of nicorandil in PMI prevention. Second, although we performed a subgroup analysis according to the diagnoses of the patients, the baseline cardiac functions differed among the enrolled patients in all 10 trials, which may account for part of the discrepancy regarding the effect of nicorandil on the PMI risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous original studies and meta-analyses have investigated various approaches to minimise the renal injury after contrast exposure. Nicorandil is primarily prescribed for patients with angina and heart failure, and 17 However, the amount of contrast agent used in each group, which may significantly affect the incidence of CIN, was not discussed in that study. 15 As no pharmacological strategies have been proven consistently effective, prophylactic hydration is treated as the cornerstone for preventing CIN in patients with renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Nijssen et al showed that no hydration was non-inferior and cost-saving in CIN prophylaxis compared with hydration, 16 suggesting that physicians should look for approaches that are potentially more effective in preventing CIN. Nicorandil is primarily prescribed for patients with angina and heart failure, and 17 However, the amount of contrast agent used in each group, which may significantly affect the incidence of CIN, was not discussed in that study. Besides, a dissertation was included, which was unlikely to have been fully peer-reviewed, and the result might not be final.…”
Section: Discussionmentioning
confidence: 99%